Islamic Doctrines on How To Live Tolerance in a Pluralistic Society - Rifki Rosyad (UIN Sunan Gunung Djati Bandung, 2022)
This study focuses on the functionalization of religion as a source of development motivation, namely creating a conducive atmosphere for increasing understanding, appreciation, and practice of religious values. All religions teach mutual respect and appreciation, therefore reviving religious dialogue is a necessity for the sustainability of the unitary state. Islam is a religion that teaches tolerance for all religions. The research method used in this research is a qualitative approach with a descriptive method because this research method discusses a phenomenon that exists in society and this research is descriptive because it tries to describe a visible phenomenon. The data collection technique used in this research is literature study. The data used in this study are primary and secondary data sources taken from books related to research. Analysis of the data used using the analytical method according to Miles and Huberman which is broadly divided into three stages, namely data collection, data presentation, and drawing conclusions. The result of this study is that the recommendation of Islam is interpreted as a whole, namely belief and equality and accountability for public behavior and politics in the lap of God.